ANALISIS COST VOLUME PROFIT SEBAGAI DASAR PERENCANAAN PENJUALAN DAN LABA YANG DIHARAPKAN PADA PT. SUTRA BENTA PERKASA PEKANBARU - Fauzana, Wulan; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Cost Volume Profit analysis shows the relationship between costs, volumes, and overall profit in calculating sales planning and corporate profit planning precisely and accurately. This study aims to determine and analyze the application of cost volume profit as the basis for planning sales and expected profits at PT. Sutra Benta Perkasa Pekanbaru. In this study using quantitative descriptive data types. The data collection technique used is the technique of interview and documentation on the financial data of PT. Sutra Benta Perkasa Pekanbaru.The analysis results show that the contribution margin and contribution margin ratio calculation can cover fixed costs and contribute profit to the company. The break-even point calculation shows that the sales condition has exceeded the break-even point. In several years, the analysis of sales and profit targets still has not been achieved due to company policies that have not been able to set targets and have not used the analysis calculations. The calculation of the margin of safety shows the company's condition is at a safe point. The measure of operating leverage shows the high sensitivity of net income to sales.Â Keywords: Cost Volume Profit, Sales Planning, Profit Planning